Eksplorasi efektivitas psikoterapi dzikir dalam mengatasi kecemasan: Sebuah kajian literatur - Safitri, Endhit Beliz (Maliki Interdisciplinary Journal, 2023)
Anxiety represents a significant global mental health challenge. This study explores the effectiveness of Dhikr psychotherapy as an alternative approach to managing anxiety through a literature review. Dhikr, a spiritual practice based on the repetition of sacred words in Islam, has emerged as a potential method for reducing anxiety. The literature review provides an overview of the concept of anxiety, types of psychotherapy, and Dhikr as one form of psychotherapy. Previous research measuring the effectiveness of Dhikr psychotherapy in reducing anxiety levels has been evaluated. The results suggest that Dhikr psychotherapy has the potential to treat anxiety, although further research is needed to understand the mechanisms and contextual variables that influence the outcomes. This study provides a foundation for further development in the field of Dhikr psychotherapy and highlights its relevance in anxiety management.